RNA silencing in the antiviral innate immune defence--role of DEAD-box RNA helicases. - Ulvila, J.; Hultmark, D.; Rämet, M. (Scandinavian Journal of Immunology, 2010)
RNA silencing is an efficient biochemical tool for gene knock downs as well as physiological phenomenon playing a major role in diverse biological processes. Recent knowledge suggests that the same protein families which mediate the experimental RNA interference (RNAi) in the fruit fly Drosophila melanogaster cells also contribute to the antiviral host defence in both invertebrate model organisms and mammals. Additionally, another branch of RNA silencing, the microRNAs (miRNAs), has been recently described in the context of host defence. In several studies, miRNAs have been shown to regulate essential immune responses. This review summarizes basic concepts of RNAi and miRNAs, especially in the context of immune defence, focusing on the newly discovered role of DEAD-box helicases in the RNA interference and antiviral host defence.